PELATIHAN PROGRAM PENDAMPINGAN PESERTA DIDIK DI SMA KRISTEN CITRA BANGSA KUPANG DALAM MELAKSANAKAN PENBELAJARAN JARAK JAUH (PJJ) - Junihot M. Simanjuntak; Agus Setio; Arnes Dela Lumban Toruan; Febri Yanti Zebua; Simson Nullik (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
The objectives of this service are: 1) To review the role of the teacher in planning and implementing distance learning so that it runs effectively in the field according to the plan that has been prepared. 2) Providing distance learning that is of interest to students in accordance with programmed learning. The form of this activity is distance learning assistance for students of Citra Bangsa Christian High School, Kupang. Participants in this activity consisted of: 1) SMA Kristen Citra Bangsa Kupang, and 2) Students in grades X, XI, and XII. This activity is carried out by teaching methods using videos, lectures, discussions and questions and answers. The results of the mentoring activities are 1) an increase in the ability of SMA Kristen Citra Kupang teachers in the preparation of distance learning programs after being given training and mentoring; and 2) there was an increase in the skills of SMA Kristen Citra Kupang teachers in implementing distance learning after being provided with assistance.